2001
DOI: 10.1002/1526-4998(200102)57:2<191::aid-ps275>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationships of benzophenone hydrazone derivatives with insecticidal activity

Abstract: A broad range of benzophenone hydrazone derivatives was prepared and tested against selected chewing insect pests, allowing the analysis of structure-activity relationships. Good activity was found only when the aromatic rings were substituted at the 4-positions with an halogen atom and a triflate or perhaloalkoxy group. In contrast, a number of substituents on the hydrazone part led to active compounds, the best results being achieved with acyl-type substituents. The excellent laboratory and greenhouse activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The first insecticide containing a hydrazone moiety is hydramethylnon , which was commercialized in 1980. In recent years, many acylhydrazone derivatives with broad‐spectrum activity were reported as insecticidal agents , including metaflumizone, which was discovered by BASF (Badische Anilin‐und Soda‐Fabriken) and then commercialized in 2007 . However, these compounds exhibit two different configurations ( cis and trans ) due to the existence of the C=N double bond.…”
Section: Introductionmentioning
confidence: 99%
“…The first insecticide containing a hydrazone moiety is hydramethylnon , which was commercialized in 1980. In recent years, many acylhydrazone derivatives with broad‐spectrum activity were reported as insecticidal agents , including metaflumizone, which was discovered by BASF (Badische Anilin‐und Soda‐Fabriken) and then commercialized in 2007 . However, these compounds exhibit two different configurations ( cis and trans ) due to the existence of the C=N double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Many hydrazone derivatives have been reported to possess broad spectrum insecticidal activity and are used as active ingredients for controlling agricultural and horticultural pests [16][17][18]. For example, the first hydrazone type insecticide, hydramethylnon, was registered for use in the United States by the Environmental Protection Agency in 1980 to control ants and cockroaches [18].…”
Section: Introductionmentioning
confidence: 99%
“…; R 1 = R 2 = R 3 = CH 3 ) which showed significant insecticidal activity . In 2001, the systematic structure–activity relationship (SAR) of benzophenone hydrazones derivatives was discussed by Böger and coworkers, who demonstrated that the hydrazone part is the only molecular area that could undertake significant structural modifications. However, to the best of our knowledge, there have been no reports on the acaricidal activities of benzophenone hydrazone derivatives against T. cinnabarinus .…”
Section: Introductionmentioning
confidence: 99%